An exploratory study of the security and privacy issues affecting the adoption of the internet of things in Vereeniging - Yeboah, Thomas (Vaal University of Technology, 2022)
Background The convergence of numerous technologies, such as real-time analytics, machine learning, ubiquitous computing, commodity sensors, and embedded systems, has resulted in the evolution of the Internet of Things. With the advent of the Internet of Things, people can be empowered, the government can be made more transparent, and information can be made more accessible. Several schools of thought argue that there is increasing worry over the possibility of the Internet of Things (IoT) diminishing people's autonomy over their own life. When there is a combination of big data and the Internet of Things, people's lives are more exposed to large businesses and political organisations. As a result, individuals have less influence over their own destinies. The present study was an ‘Exploratory Study of the Security and Privacy Issues Affecting the Adoption of the Internet of Things in Vereeniging’. The researcher adopted interpretivism as the research philosophy and the present study was inductive in its approach. The target population for this study was 30 IT specialists in Vereeniging who participated in the study through semi-structured interviews. The study has established that, to a greater extent, organisations are adopting IoT technology in their operations. The study established that smart home appliances, smart security systems, fitness trackers, wireless headphones/earbuds and so many more such items have become an intrinsic part of people’s daily lives that if we were deprived of them, people would feel a void somewhere. The study found that organisations are implementing a plethora of strategies to make sure that they are secure in their use of IoT technologies. The study also discovered that there is rampant crime emanating from human behaviour resulting in the damage of IoT infrastructure and devices in some organisations. Several fascinating discoveries on how IoT users view privacy and security have been uncovered in this research paper. The study shows that while IoT use is on the rise, so too is the growing concern around privacy and security. However, consumers choose to sacrifice these measures for the advantages and additional benefits that the technology provides to their life. While these views may remain constant for the foreseeable future, any large security incident or privacy intrusion could significantly shift beliefs. It seems that people who utilise the Internet of Things (IoT) would prefer for businesses to be more transparent about the data that is being collected and why it is being reused. They wish to get more security safeguards to safeguard their personal info. Based on these findings and previous studies, a safer IoT environment will be provided for both users and private corporations. Future IoT research studies can build on the outcomes of this study. Based on the findings in this study, the following recommendations are made: Cryptography Cryptography is helpful in safeguarding private data that is located on one network and moved to another network via a secure transmission link. Encryption can be applied to safeguard the transfer of data across an unsecured network using various cryptographic methods, such as AES, SHA-1, MD5, RSA, etc. For optimal computational efficiency, high-performance CPUs and ample memory are required. However, it's not clear how these strategies can be used efficiently at this time. As the hardware in IoT has restricted processing speed and minimal memory, significant research is necessary to correctly implement these algorithms. End to End Security Authenticity towards data can be maintained by means of many protocols, such as TLS/SSL and IPSec, which implement end-to-end security. As IoT devices have less processing power, these protocols are not feasible. As a result, security on an end-to-end basis cannot be accomplished, thus leaving the door open for hackers for data manipulation, man-in-middle attacks, denial of service attacks, and even distributed denial of service attacks. As a result, new research on the approach needed for the creation of a similar technology, analogous to TLS/SSL or IPSec, is required to safeguard data transmissions and ward off hackers. Firewall or IPS In the case of a network without firewall or intrusion prevention system, there is an open invitation to the outside world. Packet filter and Intrusion Prevention System (IPS) both have deep packet inspection capacity to manage the flow of traffic heading towards the destination. However, IoT does not provide functionality that includes packet inspection and packet filtering. Security researchers are allowed to perform research in this field, where they may build a low resource-intensive firewall to analyse and manipulate packets for IoT devices.
M. Tech. (Department of Information Technology, Faculty of Applied and Computer Sciences), Vaal University of Technology.